Portugálok Brazíliában a régi századfordulón - Szilágyi, Ágnes Judit (Acta Scientiarum Socialium, 2015)
The Portuguese in Brazil at the Turn of the 19th and the 20th Centuries Beginning in the mid-19th century, labour migrants from Portugal joined other Europeans in mass transatlantic moves to Brazil. The immigrants and their descendants were quick to organize themselves and establish mutual aid societies, libraries, newspapers and magazines. The immigrants had a deep affinity with approximation between Brazil and Portugal, and the Luso-Brazilian political thought.
Keywords: migrants; Brazil; Portugal; Luso-Brazilian political thought